Genetic divergence in arboreum cotton (Gossypium arboreum) - TOMAR, RAJANI; SINGH, P P; KOUTU, G K (The Indian Journal of Agricultural Sciences, 2012)
Fortyfive genotypes were grouped in seven, five and ten clusters in three subsequent years, i.e 2004, 2005 and 2006. The maximum number of ten clusters were formed during 2006, followed by seven and four during 2004 and 2005 respectively. Cluster I contains the maximum number of genotypes (37, 40 and 29 in 2004, 2005 and 2006 respectively), followed by cluster II. The genotypes forming single cluster were PA 405, MALJARI, KWA 227, HD 440, and PA 304 thus, they were most divergent genotypes. In general, clustering of genotypes was not related to geographic diversity. Genotypes, viz. J. Tapti, KWA 24, KWA 23, AH 65, CINA 223, and DLSA 24 were grouped together in different years thus exhibited real genetic diversity based on yield factors and quality parameters in cotton. In the year, Clusters III and V were most divergent, ie maximum inter-cluster distance in 2004, cluster II and IV in 2005 and clusters II and VI in 2006. Hence, selection of genotypes from the cluster exhibiting maximum genetic divergence would be more reliable for high heterotic response and spectrum of variation in segregating generation. The contribution of boll/plant, sympodia/plant, monopodia/plant, nodes/plant, short fibre index and oil percentage towards genetic divergence was noted in the present material. Hence, the selection of parents or donors should be based on per se performance of these characters in the form of selection indices.